Il trattamento delle lesioni massive di cuffia con lo spaziatore biodegradabile sottoacromiale - Bortolato, S.; Zacchinato, G.; Micheloni, G.M.; Salmaso, G. (Lo Scalpello - Journal, 2019)
TREATMENT OF MASSIVE ROTATOR CUFF TEARS WITH SUBACROMIAL BIODEGRADABLE SPACERSThe treatment of massive rotator cuff tears remains a challenge for orthopaedic surgeons. There are severalarthroscopic possibilities in the absence of glenohumeral arthrosis: debridement with or without tenotomy of the longhead of the biceps, partial cuff repair, use of synthetic patches and insertion of a biodegradable spacer. The aim of ourstudy was to provide a clinical and subjective analysis of patients treated in our centre using the InSpace™ balloon.The spacer is positioned in the subacromial space. This device should reduce subacromial friction so as to lead to painreduction and improvement in the range of motion. We analysed 27 patients (15 men and 12 women) treated withthis technique between December 2014 and December 2018 in our Operative Unit. Mean age was 65 years (49–71)and average follow-up time was 24.4 months. All patients had massive rotator cuff lesions associated withsubacromial bursitis. In 16 cases this lesion was associated with biceps tendinitis and, in 4 patients, with partial lesionof the subscapularis tendon. Patients underwent bursectomy and tenotomy of the long head of the biceps brachii. In 6cases the cuff was partially reconstructed using 1 or 2 anchors and side-to-side sutures. The average Constant Scorerose from 11.33/100 to 78.00. In 4 cases the Constant Score was unsatisfactory, while in the remaining patients itexceeded 85 points. The UCLA score increased from an average value of 1.33/10 points to 8.62, while the SST scorerose from 2.33/12 to 10.54 points. The final result seems to be independent of severity of the initial injury, timeelapsed and cuff reconstruction. Proper use of the spacer seems to be effective against pain and ROM restoration. Ourgoal is to continue the follow-up in these patients and to evaluate the advantages of this device in a larger sample.